Rhetoric of KH. Ahmad Nawawi's Prophecy in Improving the Religious Moderation of Students at the Mambaus Sholihin Islamic Boarding School Ciwaringin Chamber, Cirebon Regency - Maula, Minhatul; Abdurahman, Maman (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Da'wah rhetoric plays a crucial role in shaping students' understanding and attitudes towards religious teachings, including enhancing religious moderation. KH Ahmad Nawawi, as the head of Pondok Pesantren Mambaus Sholihin Babakan Ciwaringin in Cirebon Regency, utilizes his da'wah to deliver messages of religious moderation relevant to contemporary challenges. Amidst the rise of extremism and intolerance, KH Ahmad Nawawi emphasizes a da'wah approach that integrates classical religious texts with contemporary issues, using a structured and logical method in his delivery. Through effective rhetoric, he aims to instill values of moderation, tolerance, and inclusivity among students, enabling them to apply balanced Islamic teachings in their daily lives. This research aims to examine the processes of Inventio (finding materials) and Ordo Collocatio (organization) in KH Ahmad Nawawi's da'wah rhetoric in enhancing religious moderation among students at Pondok Pesantren Mambaus Sholihin Babakan Ciwaringin, Cirebon Regency. This study employs a qualitative method, using data collection techniques such as observation, interviews, and documentation. Data analysis is conducted through data collection, data reduction, data presentation, and data drawing. The findings indicate that the Inventio and Ordo Collocatio processes in KH Ahmad Nawawi's da'wah rhetoric at Pondok Pesantren Mambaus Sholihin Babakan Ciwaringin are carried out meticulously and systematically to enhance religious moderation among students. He classical religious texts with contemporary knowledge, follows social issue developments, and combines in discussions with scholars and students. His da'wah is organized in a structured manner, beginning with engaging introductions followed by relevant evidence, making it easier for students to understand and apply the principles of moderation in their daily lives according to current contexts. It is hoped that these findings will enrich the literature of the Islamic Communication and Broadcasting Studies Program at the Faculty of Da'wah and Communication, Bunga Bangsa Islamic University, Cirebon. This research makes a significant contribution to understanding the rhetorical aspects of moderate da'wah through an in-depth analysis of the process of inventio and the order of collocatio KH. Ahmad Nawawi.